(untitled) (Journal of Informatics and Mathematical Sciences, 2020)
In this paper, we have presented and illustrated the method of reduction of order for solving singularly perturbed delay differential equations. The given second order singularly perturbed delay differential equation is replaced by a pair of first order problems. These are in turn solved by initial value solvers. The integration of these initial value problems goes in the opposite direction. The applicability of this method is demonstrated by solving some model problems and the numerical results are compared with the exact solution. From the tables and figures, it is observed that the present method produces satisfactory results.